HUBUNGAN EFEKTIVITAS KEPEMIMPINAN DAN TINGKAT KEPUASAN KERJA DENGAN PRODUKTIVITAS KERJA KARYAWAN PUSKESMAS - Suharno, Sutik & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT This thesis conducted to found : (1) Are there any significant between the effeteness of leadership of the head of public healthy center with the productivity of public healthy center employee, (2) Are there any significant between the satisfaction level of work with the productivity of public healthy center employee, (3) Are there any significant relationship by together between the effectiveness of leadership of the head of public healthy center and the satisfaction level of work with productivity of public healthy center employee, (4) the fide relationship between the effeteness of leadership of the head of healthy center with the productivity of public healthy center employee compeer with the satisfaction level of work with productivity of public healthy center employee. The total population of public healthy center employee of Blora of Blora regency is 52 people, to take the sample the writer using random sampling with census system. The summary of this research are : (1) the hypothesis state â€œquest that it have any positive and significant relationship between the efecticness of the leadership of the head of public healthy center with productivity of public healthy center employeeâ€ is proved, (2) the hypothesis state â€œquest that it have any positive and significant relationship between the satisfaction level of work with productivity of workâ€ is proved (3) the hypothesis state â€œquest that it have any positive and significant relationship between the effecticnes of leadership of the head of public thy center and the satisfaction level of work with productivity of workâ€ is proved, (4) the hypothesis state â€œquest that the variable level of satisfaction level of work or more tide relationship with productivity of workâ€ is proved. Keywords : the efecticness of the leadership, the satisfaction level of work .